A comparative pharmacokinetic and pharmacodynamic study of two novel Cuban PEGylated rHuEPO versus MIRCERA® and ior®EPOCIM - Gledys Reynaldo; Leyanis Rodríguez; Roberto Menéndez; Joaquín Solazábal; Daniel Amaro; María de los A. Becquer; Yamila Colom; Haydee Gil; Juan C. Polo; Gilberto Castañeda; Braulio Jiménez-Vélez; Jorge Duconge; et al. (Journal of Pharmacy & Pharmacognosy Research, 2018)
Context: The recombinant human erythropoietin (rHuEPO) stimulates the erythropoiesis process. Because this glycoprotein has a short half-life, it needs to be administrated two to three times a week. One of the technics to solve this issue is the PEGgilation.